Herald - Macleod, Caitlin (Centre for Film and Media Studies, 2017)
The original idea behind Herald was to create a South African Downton Abbey (ITV and PBS, 2010 -2015). Historical television is currently popular and Downton is appealing because it communicates interesting history, finds comedy in the manners and behaviours of the day and indulges in the visual pleasures of opulent aristocratic society. A historical setting is as foreign and exciting as a fantasy realm but it can still provide a platform to explore themes that are relevant and familiar to a contemporary viewer. Members of local government, military officers and other nobles and wealthy Britons at the Cape lived aristocratic lives not unlike the fictional inhabitants of Downton and yet a wholesale pastiche of the structure of Downton or the conventions of the period drama genre is inappropriate. The racial tensions that have defined the colonial and postcolonial periods of South African history and the Eurocentric, androcentric approach to that history necessitate a new approach. It is with this in mind that I have attempted to create a television miniseries inspired by the traditional period drama and by Downton Abbey specifically, but remoulded by the contexts of past and present day South Africa. I had several main goals in mind for this miniseries: to provide South Africans with entertaining television that tells local stories and, in so doing, encourage South Africans to engage with their own history; to grapple with contentious issues of the present such as race, gender and land, by exploring the past; to place strong black, Malay and female characters at the center of history and give them the agency to effect history; to provide a critique of the British and their actions at the Cape.